Implementation of Village Fund-Based Food Security Programs in Coastal Communities: A Policy Implementation Perspective from Bintan Pesisir District, Indonesia - Ika Yuliawati; Armauliza Septiawan; Fitri Kurnianingsih (Journal of Governance and Social Policy, 2026)
Food security is a national development priority supported through the utilization of Village Funds based on local potential. This study aims to analyze the implementation of the Village Fund-based Food Security Program in Bintan Pesisir District, Bintan Regency. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Data analysis was conducted using the policy implementation model of Van Meter and Van Horn. The findings indicate that the program has been implemented through various activities, including food crop cultivation, fisheries development, seafood processing, and community group empowerment. However, several challenges remain, such as limited human resources, low community participation, weak monitoring and evaluation mechanisms, and the geographical conditions of coastal areas. The study concludes that strengthening the capacity of village officials, increasing community participation, and enhancing program supervision are essential to improving the effectiveness of Village Fund-based food security programs.